前瞻綠色航太推進與能源效益之燃料-水合技術開發研究 - 趙怡欽; 許紘瑋 (2012)
計畫編號:NSC101-2221-E006-067-MY3 執行機構:國立成功大學航空太空工程學系 研究期間:2012-08~2013-07 本計畫「前瞻綠色航太推進與能源效益之燃料-水合技術開發研究」擬以三年為期(101年8月1日至104年7月31日止)，結合氣體水合(gaseous-fuel hydrate)與粉狀金屬-水混合燃料(例如鋁粉與水混合之高能推進劑)的特性，著手進行可兼具太空推進與能源效益之燃料水合技術研究開發，以期可藉由該技術之發展，有效提升水合燃料(fuel hydrate)的應用性。研究內容依規劃包含：氣體水合、粉體可燃物-水混合之固體燃料、粉體-氣體水合物等合成技術開發，以及相關合成燃料之物性與燃燒特性診測等。透過此一研究的開發，除了可更加了解氣體燃料水合的機制，亦可掌握粉體物質如何透過界面處理穩定其活性，並與水結合固化形成高能燃料。此外，利用對水合與粉體-水混合機制的更深入認識，更可進一步評估如何將高能粉體物質合成於水合燃料中，促使水合燃料中原只扮演容器角色的水轉變為穩定於其中的提供燃燒氧氣的氧化劑(oxidizer)來源，如此經處理後的水合燃料即可以固體型態直接燃燒而無須進行水的處理，且由於無需外在空氣供給助燃，燃燒後的廢氣也將因不含氮氣而有利於二氧化碳回收，有利於減少碳排放。這些相關各種水合技術的開發與應用，在國際間也是剛剛開始投入研究，由於水合燃料與後續之合成為高能固體燃料所需的原料均可以於國內取得，以此開發之技術加以合成，甚至自然生成的水合甲烷(methane hydrate)也可自台灣周圍陸緣海域取得，計畫之完成，除對國內太空火箭推進研究產生直接性的影響，促使國家得以與國際同步，自主掌握高能推進之研發能量外，對於國家未來以水合甲烷為架構的能源供給與應用，甚至減碳技術的開發，均將產生莫大的助益。 The object of this three-year research project, “Research and Development of the Fuel Hydrate Techniques for Advanced Green Aerospace Propulsion and Energy Perspectives” (Period: 2012/08/01~2015/07/31), is to develop the proposed the advanced general hydrate techniques in terms of fuel-hydrate and propellant-hydrate for the perspective applications in the advanced “Green” aerospace propulsion and energy engineering. The proposed research will include the development of various fuel- and propellant-hydrate techniques including: gaseous-fuel hydrate, solid-fuel particle-hydrate, particle-gaseous fuel-hydrate, as well as the studies of the physical, chemical and combustion characteristics of these synthesized hydrated fuels and propellants. The current research will not only provide further hydrate techniques to synthesize highly energetic “green” fuels and propellants for perspective aerospace propulsion and energy applications, but also go further beyond the conventional role of water in the hydrate as a container of fuels to the role of oxidizer provider to facilitate energetic combustion without breathing external air so that there will be no nitrogen content in the product flue gases and the carbon dioxide concentration is very high to facilitate high-efficient carbon capture to achieve the “Green” propellant and energy perspectives. In this research project, the proposed concepts of synthetic hydrate techniques are fairly new and novel even among the advanced international combustion communities, such as the United States and Japan, and fortunately all raw materials required to synthesize the fuel-hydrates can easily be acquired locally, even the methane hydrate has been found abundant in the land shell around Taiwan strait and the island. The development of the proposed “Green” energetic propellant hydrate will have direct impact on the enhancement of our aerospace rocket propulsion technology as well as the future “low and zero carbon emission” “Green” energy supply and utilization.